Analisis Transmisi Data dan Kecepatan Performa Website Laboratorium VTE Untirta - Didik Aribowo; Dede Saprudin; Rafly Permana Putra; Sahmawati Sahmawati; Jenice Fautsa Ro Intan Sagala; Jessen Parulian Sianturi; Aghna Ath’aillah Al-Fawwaz (Pusat riset dan Inovasi Nasional, 2025)
The purpose of this study is to evaluate how effective the laboratory information system is in terms of data transmission and website speed at the UNTIRTA VTE Laboratory. To conduct this study, a literature review and direct observation of the data sending and receiving process, as measured by PageSpeed ​​Insights, were used. The results showed that overall, the website performance was good, with optimal FCP and LCP values ​​on desktop and mobile devices. However, elements such as Interaction to Next Paint (INP) and Speed ​​Index (SI) require additional improvements to improve interactivity and access speed. The student dashboard page is considered the main activity center, according to the analysis of user access pattern data. However, pages with large file sizes require better data transmission management to avoid bottlenecks. The student dashboard page is considered the main activity center, according to the analysis of user access pattern data. However, pages with large file sizes require better data transmission management to avoid bottlenecks. This study provides an overview of how effective data transmission and user experience are on the laboratory website and suggests the development of infrastructure and website optimization elements, such as caching and file size reduction. These results contribute to the continuous improvement of the laboratory website, which is very important to meet the data and information service needs of UNTIRTA VTE Laboratory users in real-time.